2001
DOI: 10.1016/s1386-6532(01)00158-5
|View full text |Cite
|
Sign up to set email alerts
|

Retrovirus infections in a sample of injecting drug users in Rio de Janeiro City, Brazil: prevalence of HIV-1 subtypes, and co-infection with HTLV-I/II

Abstract: Moderately high seroprevalences were found for both HIV-1 and HTLV-I/II infections, HIV-1/HTLV-I co-infections being of special concern. A non-statistically significant higher prevalence of F subtype was observed, when compared with the distribution of F/B subtypes among Brazilian patients from other exposure categories. No recent HIV-1 infections were detected, but a limitation of the "sensitive/less-sensitive" testing strategy was made evident.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
40
4
10

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(62 citation statements)
references
References 32 publications
(42 reference statements)
8
40
4
10
Order By: Relevance
“…The lack of correlation between subtypes and clinical/epidemiological data has also been reported by other authors in Brazil (Guimarães et al 2001, Turchi et al 2002.…”
Section: Discussionsupporting
confidence: 72%
“…The lack of correlation between subtypes and clinical/epidemiological data has also been reported by other authors in Brazil (Guimarães et al 2001, Turchi et al 2002.…”
Section: Discussionsupporting
confidence: 72%
“…HTLV-1 is more frequent among injection drug users in Brazil and New York [34][35][36][37][38] , whereas HTLV-2 is more prevalent in injection drug users in other locations in North America and in Europe [39][40][41][42][43][44] . In 2001, the fi rst cases of HTLV-1 transmission through organs that were transplanted from asymptomatic infected donors were reported in Europe; three donor organ recipients developed subacute myelopathy shortly after transplantation 45 .…”
Section: Modes Of Htlv Transmissionmentioning
confidence: 99%
“…High-risk behaviors, such as unprotected sex 50 , multiple partners [51][52][53] , sexual intercourse with injection drug users 34,39 , sexual partners from HTLV-endemic areas 54,55 , certain sexual practices 53 , and a history of other sexually transmitted diseases [50][51][52][53][54][55][56][57][58][59][60] , have been identifi ed as risk factors for HTLV infection. In addition, the epidemiology of HTLV, particularly its tendency to occur in clusters, has enabled the identifi cation of groups who are at risk for exposure, including injection drug users 34,56,59 , sex workers 50,[55][56][57][58][59][60][61][62] , men who engage in intercourse with other men 52,53,56 , recipients of blood transfusions in Brazil before November 1993 63 , and sexual partners of known HTLV carriers [64][65][66] (Figure 2).…”
Section: Sexual Transmissionmentioning
confidence: 99%
“…Using data from Brazilian studies, peer-reviewed papers and abstracts, we integrate biological findings from serological analyses of HIV and viral hepatitis, HIV incidence estimation through the use of STAHRS (serologic testing algorithm for recent HIV seroconversion; Janssen et al 1998), and behavioral and epidemiologic data from recent surveys carried out in 1994-6 (Telles et al 1997, Guimarães et al 2001(Teixeira et al 2004, Hacker et al 2005. Both surveys recruited patients from the Rio de Janeiro drug scene, using a targeted sampling strategy (Watters & Biernacki 1989).…”
Section: Assessing Drug Injecting Scenes: Challenges and Alternativesmentioning
confidence: 99%
“…In three different Brazilian cities (Rio de Janeiro, Salvador, and Santos), with mature epidemics (Carvalho et al 1996, Telles et al 1997, Andrade et al 1998, Guimarães et al 2001, Mesquita et al 2001) and well-established preventive programs (Telles 1999, Andrade et al 2001, Mesquita et al 2003, declining HIV/AIDS epidemics have been reported in the population of injection drug users.…”
Section: Recent Findings From Brazilian Studiesmentioning
confidence: 99%